HUBUNGAN ANTARA ADVERSITY INTELLIGENCE DENGAN HEALTH-RELATED QUALITY OF LIFE PADA MAHASISWA S1 ANGKATAN 2010 FAKULTAS KEDOKTERAN UNIVERSITAS DIPONEGORO SEMARANG - Erysa Choirunnisa; Farida Hidayati; Unika Prihatsanti (Jurnal EMPATI, 2012)
This research aimed to find out whether variables Adversity Intelligence having correlation with variable Health-related Quality of Life. Population in this research is student class 2010 of Medicine Faculty, Diponegoro University and using proportional random sampling, got 198 students being sample. Data were collected by Adversity Intelligence (33 item) and Health-related Quality of Life (27 item). This research find that there is a positive correlation between Adversity Intelligence and Health-related Quality of Life. Students who can  overcome his/her difficulty having a higher quality of life than student who feel helpless. There is no difference in Health-related Quality of Life level based on sex, housing type and course.